Silicon dioxide material and preparation method thereof and application thereof in lithium ion battery

By bombarding silica and silicon with high-energy electron beams under vacuum and coated with carbon or conductive polymers, a high-first-effect silicon oxide material was prepared, which solved the problem of low Coulomb efficiency for the first time and significantly improved the performance of the battery.

CN115275142BActive Publication Date: 2025-03-14HEFEI GUOXUAN HIGH TECH POWER ENERGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210897826.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-28
Publication Date
2025-03-14
Estimated Expiration
2042-07-28

AI Technical Summary

Technical Problem

Silicon oxide materials have low first-time Coulomb efficiency in lithium-ion batteries, limiting their practical application.

Method used

By mixing silica powder, silicon powder, metal powder and molten salt, pressing the blank and bombarding high-energy electron beam under vacuum, obtaining a silicon oxide material precursor, and then carbon coating or conductive polymer coating, a high-first-effect silicon oxide material is prepared.

Benefits of technology

The first Coulomb efficiency and cycle stability performance of silicon oxide materials are improved, making it an excellent choice for lithium-ion battery negative electrode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115275142B_ABST
    Figure CN115275142B_ABST
Patent Text Reader

Abstract

The present invention discloses silicon dioxide material, its preparation method and its application in lithium-ion batteries. The process comprises: mixing silicon dioxide powder, silicon powder, metal powder and molten salt; pressing a blank, bombarding the blank with a high-energy electron beam under vacuum conditions; crushing the obtained silicon dioxide material precursor, carbon coating or / and conductive polymer coating, and obtaining a carbon-coated or / and conductive polymer-coated metal-reduced silicon dioxide material. The present invention uses a high-energy electron beam to cause silicon dioxide and silicon to undergo an alloying reaction and then performs metal reduction, followed by carbon coating or / and conductive polymer coating to obtain a carbon-coated or / and conductive polymer-coated metal-reduced high-initial-efficiency silicon dioxide material. Since the metal reduction generates the corresponding oxides and silicates, the subsequent consumption of lithium ions is reduced, thereby improving the initial coulombic efficiency and cycle stability of the silicon dioxide material, and is an excellent choice for negative electrode materials for lithium-ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to silicon dioxide materials, a preparation method thereof, and applications thereof in lithium-ion batteries. Background Art

[0002] The cruising range of electric vehicles is related to changes in people's needs and the future development of the automotive industry. In order to achieve an energy density of 300wh / kg for power batteries, it is an inevitable choice to replace the commercialized lithium iron phosphate and lithium cobalt oxide with ternary materials as the positive electrode material of lithium-ion batteries; and replacing the graphite negative electrode with silicon-carbon materials to exponentially increase the energy density of the battery is also an inevitable trend in the development of the new energy vehicle industry.

[0003] Because silicon has a lower platform potential and a very high theoretical capacity (3800mAh / g, Li 15 Si4; 4200mAh / g, Li 22 Si5 has the advantages of high surface area, high tap density and simple preparation, so it has great application prospects.

[0004] However, silicon material as negative electrode material will undergo huge volume changes during the charging and discharging process, causing the battery performance to decay sharply; while silicon oxide material has a higher theoretical capacity and lower volume expansion and has gradually attracted attention, but the low first coulombic efficiency of silicon oxide material limits its practical application. Summary of the invention

[0005] The purpose of the present invention is to provide a new high-initial-effective silicon dioxide material and its preparation method and application. Compared with the mainstream products prepared by traditional methods, the high-initial-effective silicon dioxide material prepared by this method has better performance.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] A method for preparing silicon dioxide material comprises the following steps:

[0008] 1) Mix silica powder, silicon powder, metal powder and molten salt;

[0009] 2) Pressing the mixed materials into green sheets, bombarding the green sheets with high-energy electron beams under vacuum conditions to obtain silicon dioxide material precursors;

[0010] 3) The obtained silicon monoxide material precursor is crushed, carbon-coated or / and conductive polymer-coated to obtain a carbon-coated or / and conductive polymer-coated metal-reduced silicon monoxide material.

[0011] In step 1) of the above method, the metal is one or a mixture of at least two of lithium, sodium, magnesium, potassium, calcium, and aluminum;

[0012] The molten salt is one or a mixture of at least two of lithium chloride, sodium chloride, potassium chloride, magnesium chloride and sodium fluoride;

[0013] The D50 of silicon dioxide powder and silicon powder is 1-15 μm, and the particle size of metal powder is 100-400 mesh;

[0014] The molar ratio of silicon dioxide to silicon may be 1:(0.75-1.5), specifically 1:1, 1:1.25;

[0015] The molar ratio of metal to silicon dioxide may be 1:(0.25-10), specifically 1:1, 1:1.1;

[0016] The ratio of the molten salt to the total molar number of silicon dioxide and silicon may be 5-15:1, specifically 5:1, 6:1 or 10:1;

[0017] The mixing methods include VC mixing, fusion, and three-dimensional mixing;

[0018] In step 2) of the above method, the pressing pressure of the green sheet may be 100-200N;

[0019] The vacuum condition is 1-0.1 Pa, specifically 0.1 Pa;

[0020] When the high-energy electron beam bombards the blank, the voltage between the cathode and cathode of the electron beam can be 20-300KV;

[0021] In step 3) of the above method, the pulverization method includes grinding, mechanical pulverization, and air flow pulverization;

[0022] Preferably, the D50 of the crushed material is 3-20 μm;

[0023] The carbon coating and / or conductive polymer coating method includes one or a combination of at least two of solid phase coating, liquid phase coating and gas phase coating.

[0024] The thickness of the obtained coating layer is 1-50nm;

[0025] The conductive polymer may be one or a mixture of at least two of polyacetylene, polythiophene, polypyrrole, polyaniline, polyphenylene, polyphenylene vinylene and polybisyne.

[0026] The silicon oxide material (carbon-coated or / and conductive polymer-coated metal-reduced silicon oxide material) prepared by the above method for preparing silicon oxide material also falls within the protection scope of the present invention.

[0027] The silicon monoxide material is used as a negative electrode material in the preparation of a secondary battery.

[0028] The secondary battery may specifically be a lithium-ion battery.

[0029] The present invention also provides a secondary battery, wherein the secondary battery uses the silicon monoxide material as a negative electrode material.

[0030] The present invention also provides an electrical device, which includes the secondary battery.

[0031] The beneficial effects of the present invention are as follows: the preparation method of the silicon dioxide material of the present invention is different from the traditional preparation method of the silicon dioxide material. The present invention uses a high-energy electron beam to cause silicon dioxide and silicon to undergo an alloying reaction and then performs metal reduction, followed by carbon coating or / and conductive polymer coating to obtain a carbon-coated or / and conductive polymer-coated metal-reduced high-initial-efficiency silicon dioxide material. Since the metal reduction generates corresponding oxides and silicates, the subsequent consumption of lithium ions is reduced, thereby improving the initial coulombic efficiency and cycle stability of the silicon dioxide material, and is an excellent choice for negative electrode materials for lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 is a SEM image of the silicon dioxide material prepared in Example 1 of the present invention;

[0033] Figure 2 It is the first charge and discharge diagram of the carbon-coated silicon oxide material prepared by Example 1 of the present invention and the conventional method respectively;

[0034] Figure 3 1 is a charge-discharge cycle diagram of the carbon-coated silicon oxide material prepared by Example 1 of the present invention and the conventional method respectively;

[0035] Figure 4 This is a SEM image of the high first-efficiency silicon dioxide material prepared in Example 2 of the present invention;

[0036] Figure 5 It is the first charge-discharge diagram of the carbon-coated silicon oxide material obtained by metal reduction in Example 2 of the present invention and the conventional method respectively;

[0037] Figure 6 1. The charge-discharge cycle diagram of the carbon-coated silicon oxide material obtained by metal reduction in Example 2 of the present invention and the conventional method respectively;

[0038] Figure 7 This is a SEM image of the high first-efficiency silicon dioxide material prepared in Example 3 of the present invention;

[0039] Figure 8It is the first charge-discharge diagram of the carbon-coated silicon oxide material prepared by Example 3 of the present invention and the electron beam triggered reaction without adding reducing metal;

[0040] Fig. 9 It is a charge-drop cycle diagram of carbon-coated silicon dioxide material prepared by Example 3 of the present invention and electron beam triggered reaction without adding reducing metal. DETAILED DESCRIPTION

[0041] The present invention is further described in detail below in conjunction with specific embodiments, and the examples provided are only for illustrating the present invention, rather than for limiting the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art, and do not constitute a limitation of the present invention in any way.

[0042] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.

[0043] Example 1

[0044] A method for preparing silicon dioxide material comprises the following steps:

[0045] Silica powder with a D50 of 3 μm, silicon powder, 100-mesh lithium metal powder, and potassium chloride are mixed by VC and pressed with a force of 100 N, wherein the molar amount of silicon dioxide: the molar amount of silicon is 1:1, the molar amount of lithium metal: the molar amount of silicon dioxide is 1:1, and the molar amount of potassium chloride: (molar amount of silicon dioxide + molar amount of silicon) = 5:1; vacuum is drawn to make the vacuum degree in the furnace 0.1 Pa, and after bombardment reaction by a high-energy electron beam (the voltage between the cathode and the anode is 27 KV), it is crushed into a silicon oxide material precursor with a D50 of 4 μm by mechanical crushing;

[0046] The obtained silicon oxide material precursor is then solid-phase carbon-coated (the carbon source is asphalt, the mass of asphalt is 5% of the silicon oxide material precursor, N2 atmosphere, calcined at 800°C for 2h) to obtain carbon-coated lithium-reduced silicon oxide material (carbon layer thickness is 10nm).

[0047] The morphology of the silicon dioxide material obtained in Example 1 is detected by SEM. Figure 1 shown.

[0048] Depend on Figure 1 It can be seen that in the silicon monoxide material prepared in Example 1, carbon is uniformly coated on the surface of silicon monoxide.

[0049] The silicon oxide material prepared in Example 1 was used as the negative electrode material to prepare button batteries. At the same time, the carbon-coated silicon oxide material prepared by the conventional method (prepared by solid-phase carbon coating of a conventional silicon oxide material precursor (silicon and silicon dioxide are mixed and alloyed in a molar ratio of 1:1) with asphalt as the carbon source, wherein the mass of asphalt is 5% of the conventional silicon oxide precursor, calcined at 800°C in N2 atmosphere) was used as the negative electrode material to prepare button batteries. Both were subjected to the first charge and discharge test and the cycle performance test. The results are as follows: Figure 2 and Figure 3 shown.

[0050] The specific operation is as follows: the silicon oxide material prepared in Example 1 or the carbon-coated silicon oxide material prepared by the conventional method is mixed with the graphite material (S360-L1 graphite product name Beiterry) on the market with a gram capacity of 600mAh / g, and then mixed with LA133 and a conductive agent (Super-P) at a mass ratio of 80:10:10, coated on a copper foil, and vacuum dried and rolled to prepare a negative electrode sheet; a metal lithium sheet is used as the counter electrode, TC061 is used as the electrolyte, and a polypropylene microporous membrane is used to assemble a CR2026 button battery in a glove box filled with inert gas. The charge and discharge test of the button battery is carried out on the Shenzhen Xinwei test system, at room temperature, 0.1C constant current charge and discharge, and the charge and discharge voltage is limited to 0.005~1.5V.

[0051] Depend on Figure 2 It can be seen that compared with the carbon-coated silicon oxide material prepared by conventional methods, the button cell made of the high first efficiency silicon oxide material prepared in Example 1 significantly improves the first coulombic efficiency of the silicon oxide material.

[0052] Depend on Figure 3 It can be seen that compared with the carbon-coated silicon oxide material prepared by the conventional method, the button cell made of the high first-efficiency silicon oxide material prepared in Example 1 significantly improves the cycle performance of the silicon oxide material.

[0053] Example 2

[0054] A method for preparing silicon dioxide material comprises the following steps:

[0055] Silica with a D50 of 4 μm, silicon, 200 mesh lithium metal powder, and sodium chloride were mixed by VC and pressed with a force of 200 N, wherein the molar amount of silica: molar amount of silicon was 4:5, the molar amount of lithium metal: molar amount of silica was 1:1.1, and the molar amount of sodium chloride: (molar amount of silica + molar amount of silicon) = 10:1. The vacuum degree in the furnace was 0.1 Pa, and after bombardment reaction by a high-energy electron beam (the voltage between the cathode and the anode was 30 KV), it was crushed mechanically to form a high-efficiency silicon oxide material precursor with a D50 of 5 μm;

[0056] The obtained high first-effect silicon oxide material precursor is then subjected to gas phase carbon coating (the carbon source is methane, the mass of methane is 3% of the silicon oxide material precursor, and sintered in a CVD furnace at 1000°C for 2h) to obtain a carbon-coated lithium-reduced silicon oxide material (carbon layer thickness 10nm).

[0057] The morphology of the silicon dioxide material obtained in Example 2 is detected by SEM. Figure 4 shown.

[0058] Depend on Figure 4 It can be seen that in the carbon-coated silicon oxide material prepared in Example 2, carbon is uniformly coated on the surface of silicon oxide.

[0059] The high first-efficiency silicon oxide material prepared in Example 2 was used as the negative electrode material to prepare a button battery. At the same time, the silicon oxide material (silicon dioxide molar amount: silicon molar amount of 4:5) was mixed and vacuum alloyed to prepare silicon oxide by metal reduction in a conventional method. The silicon oxide and lithium powder were calcined at high temperature (sintered at 800°C for 5h), wherein the lithium metal molar amount: silicon dioxide molar amount was 1:1.1, and gas-phase carbon coating (carbon source was methane, the mass of methane was 3% of the silicon oxide material, and the CVD furnace was sintered at 1000°C for 2h) was used as the negative electrode material to prepare a button battery. Both were subjected to the first charge and discharge test and the cycle performance test. The structure is as follows Figure 5 and Figure 6 shown.

[0060] A CR2026 button cell was prepared and tested according to the method in Example 1.

[0061] Depend on Figure 5 It can be seen that compared with the silicon oxide material reduced by metal using the conventional method, the button cell made of the high first efficiency silicon oxide material prepared in Example 2 significantly improves the first coulombic efficiency of the silicon oxide material.

[0062] Depend on Figure 6 It can be seen that compared with the silicon oxide material reduced by metal using the conventional method, the button cell made of the high first-efficiency silicon oxide material prepared in Example 2 significantly improves the cycle performance of the silicon oxide material.

[0063] Example 3

[0064] A method for preparing silicon dioxide material comprises the following steps:

[0065] Silica with a D50 of 4 μm, silicon, 200 mesh magnesium metal powder, and magnesium chloride were mixed by VC and pressed with a force of 200 N, wherein the molar amount of silica: molar amount of silicon was 1:1, the molar amount of magnesium metal: molar amount of silica was 1:1, and the molar amount of magnesium chloride: (molar amount of silica + molar amount of silicon) = 6:1. The vacuum degree in the furnace was 0.1 Pa, and after bombardment reaction by a high-energy electron beam (the voltage between the cathode and the anode was 27 KV), it was crushed into a silicon oxide material precursor with a D50 of 5 μm by mechanical crushing;

[0066] The obtained silicon oxide material precursor is then solid-phase carbon-coated (the carbon source is asphalt, the mass of asphalt is 5% of the silicon oxide material precursor, N2 atmosphere, calcined at 800°C) to obtain a carbon-coated lithium-reduced high-efficiency silicon oxide material (the carbon layer thickness is 10 nm).

[0067] Depend on Figure 7 It can be seen that in the high first-efficiency silicon iodine material prepared in Example 3, carbon is uniformly coated on the surface of silicon iodine.

[0068] The high first-efficiency silicon dioxide material prepared in Example 3 was used as the negative electrode material to prepare a button battery. At the same time, the electron beam was used to trigger the reaction without adding reducing metal, and the same solid-phase coated silicon dioxide material was used as the negative electrode material (silicon dioxide, silicon, and magnesium chloride with a D50 of 4 μm were mixed by VC and pressed using a force of 200N, wherein the molar amount of silicon dioxide: the molar amount of silicon was 1:1, and the molar amount of magnesium chloride: (molar amount of silicon dioxide + molar amount of silicon) = 6:1. The vacuum degree in the furnace was 0.1 Pa. After bombardment by a high-energy electron beam (the voltage between the anode and cathode was 27 KV), it was mechanically crushed to form a silicon dioxide material precursor with a D50 of 5 μm; then the obtained silicon dioxide material precursor was solid-phase carbon-coated (the carbon source was asphalt, the mass of asphalt was 5% of the silicon dioxide material precursor, N2 atmosphere, and calcined at 800°C) to obtain a carbon-coated lithium-reduced high-first-efficiency silicon dioxide material to prepare a button battery. Both were subjected to the first charge and discharge test and cycle performance test, and the structure was as follows Figure 8 and Fig. 9 shown.

[0069] Depend on Figure 8 It can be seen that compared with the electron beam triggered reaction without adding reducing metal using the same solid phase coated silicon oxide material, the button cell made of the high first efficiency silicon oxide material prepared in Example 3 significantly improves the first coulombic efficiency of the silicon oxide material.

[0070] Depend on Fig. 9 It can be seen that compared with the electron beam triggered reaction without adding reducing metal using the same solid phase coated silicon oxide material, the button battery made of the high first efficiency silicon oxide material prepared in Example 3 significantly improves the cycle performance of the silicon oxide material.

[0071] The present invention has been described in detail above. For those skilled in the art, without departing from the purpose and scope of the present invention, and without the need to carry out unnecessary experimental conditions, the present invention can be implemented in a wide range under equivalent parameters, concentrations and conditions. Although the present invention provides specific embodiments, it should be understood that the present invention can be further improved. In a word, according to the principles of the present invention, the application is intended to include any changes, uses or improvements to the present invention, including departure from the disclosed scope in the application, and changes made with conventional techniques known in the art.

Claims

1. A method for preparing silicon dioxide material, comprising the following steps: 1) Mix silica powder, silicon powder, metal powder and molten salt; The molar ratio of silica to silicon is 1:(0.75-1.5); The molar ratio of metal to silica is 1:(0.25-10); The ratio of molten salt to the total molar number of silicon dioxide and silicon is 5-15:1; In step 1), the metal is one or a mixture of at least two of lithium, sodium, magnesium, potassium, calcium, and aluminum; The molten salt is one or a mixture of at least two of lithium chloride, sodium chloride, potassium chloride, magnesium chloride and sodium fluoride; 2) The mixed materials are pressed into green sheets, and under vacuum conditions, high-energy electron beams are used to bombard the green sheets to obtain silicon dioxide material precursors; 3) crushing the obtained silicon oxide material precursor, carbon coating or / and conductive polymer coating, to obtain carbon-coated or / and conductive polymer-coated metal-reduced silicon oxide material; The vacuum condition is 1-0.1 Pa; When the billet is bombarded by a high-energy electron beam, the voltage between the cathode and cathode of the electron beam is 20-300KV.

2. The method for preparing silicon dioxide material according to claim 1, characterized in that: The D50 of silica powder and silicon powder is 1-15 μm, and the particle size of metal powder is 100-400 mesh.

3. The method for preparing silicon dioxide material according to claim 1 or 2, characterized in that: In step 2), the pressing pressure is 100-200N.

4. The method for preparing silicon dioxide material according to claim 1 or 2, characterized in that: In step 3), the pulverization method includes grinding, mechanical pulverization, and air flow pulverization; The D50 of the crushed material is 3-20μm.

5. The method for preparing silicon dioxide material according to claim 1 or 2, characterized in that: The carbon coating and / or conductive polymer coating method comprises one or a combination of at least two of solid phase coating, liquid phase coating and gas phase coating; The thickness of the obtained coating layer is 1-50nm; The conductive polymer is one or a mixture of at least two of polyacetylene, polythiophene, polypyrrole, polyaniline, polyphenylene, polyphenylene ethylene and polybisyne.

6. Silicon oxide material prepared by the method for preparing silicon oxide material according to any one of claims 1 to 5.

7. Use of the silicon dioxide material according to claim 6 as a negative electrode material in the preparation of a secondary battery.

8. A secondary battery comprising the silicon monoxide material according to claim 6.

9. An electric device comprising the secondary battery according to claim 8.

Citation Information

Patent Citations

  • Silicon oxide composite negative electrode material for lithium ion battery and preparation method of silicon oxide composite negative electrode material

    CN109524650A

  • Preparation method of silicon monoxide composite negative electrode material and product thereof

    CN112086630A